Python Robotics Projects : Build smart and collaborative robots using Python. - Vaish, Diwakar (Packt Publishing, 2018)
Robotics is emerging to be a 100 billion industry by 2020 based on current trends and is about to create the largest technological revolution. This book will cover everything you need to know about robotics and will help you to build smart robots using Python.